Comparative study of the electroencephalographic activity at professional handball and fencers players - Enescu Bieru, D.; Calina, M. L.; Gusti, A.; Dinu, V.; Cosma, G.; Dragomi,r M. M.; Fortan, C.; Popescu, C. (Journal of Physical Education and Sport, 2010)
Our purpose was to study the electroencephalographic activity of professional handball and fencers players, to compare the obtained data and to identify a possible neurophysiologic pattern associate to practiced sportive activity.